(3GdUhJ heGgjJg hGdaQb Hjf GdXGA hGdVGOs - (3Bd cGTa GdZWGA, eMeO QVG Hf gGOj Hf YHGS, J (B1366 (3g`s ((3GdfLas)
(3ChdgG (B:s
(3GdMeO ddg cKjQG hGdUdGI Ydi eMeO hBdg(B... (3hHYO agPG eG ChUdfj Edjg GdHMK ef LhGH eSGFd(B...s
(3BNQgG (B:s
(3hJQJbj GdMQha GdgLGFjI GdYQHjI Edi JSYI hKdGKjf(B. (3gPG eG CQOJ LeYg hJCdjag ef CUM eUGOQg hCJbf ehGQOg(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agGQS GdehShYI GdTYQjIs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GddZIs